2001
DOI: 10.1002/gps.479
|View full text |Cite
|
Sign up to set email alerts
|

Validation and normative data of health status measures in older people: the Islington study

Abstract: The SF-12 and HSQ-12 are acceptable and valid as health status instruments in large community-based studies of older people. The HSQ-12, but not the SF-12, is acceptable and valid for people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 25 publications
4
74
0
Order By: Relevance
“…For a general population sample of 173 individuals aged 75+ from Italy, Savioa et al [20] reported higher problem frequencies in pain/discomfort (67.3%) and anxiety/depression (53.3%), similar frequencies in usual activities (37.3%) and self-care (21.8%), and a lower frequency in mobility (40.0%); the EQ-VAS score was 68.0. Surveys which used the SF-12 in the elderly population samples also reported impaired physical health but average mental health summary scores [20,21,24], similar to our survey. Yet, similar to our results, mean MCS scores reported by these surveys did not differ from general population average, indicating that mental health does not deteriorate with age.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For a general population sample of 173 individuals aged 75+ from Italy, Savioa et al [20] reported higher problem frequencies in pain/discomfort (67.3%) and anxiety/depression (53.3%), similar frequencies in usual activities (37.3%) and self-care (21.8%), and a lower frequency in mobility (40.0%); the EQ-VAS score was 68.0. Surveys which used the SF-12 in the elderly population samples also reported impaired physical health but average mental health summary scores [20,21,24], similar to our survey. Yet, similar to our results, mean MCS scores reported by these surveys did not differ from general population average, indicating that mental health does not deteriorate with age.…”
Section: Discussionsupporting
confidence: 75%
“…Research concerned with the total adult population (18 and older) similarly found significant gender differences; i.e. females typically reported more problems in EQ-5D [10,14,20] dimensions and lower PCS and MCS scores [21]. In comparison to studies that solely analyzed elderly cohorts the differences were much less pronounced though.…”
Section: Discussionmentioning
confidence: 99%
“…74 The validity of the Nottingham Health Profile, SF-12 and EQ-5D for people with dementia is also questionable. [75][76][77] The content, format and instructions of HRQoL instruments must be appropriate to people with dementia, given their cognitive difficulties. By definition, generic measures are not necessarily designed in a way that makes them easy for a person with dementia to complete.…”
Section: Generic Measuresmentioning
confidence: 99%
“…Research concerned with the total adult population (18 and older) similarly found significant gender differences; i.e. females typically reported more problems in EQ-5D [10,14,20] dimensions and lower PCS and MCS scores [21]. In comparison to studies that solely analyzed elderly cohorts the differences were much less pronounced though.…”
Section: Discussionmentioning
confidence: 96%